Mercury methylation and demethylation in highly contaminated sediments from the Deûle River in Northern France using species-specific enriched stable isotopes. Issue 1 (25th November 2014) - Ouddane, Baghdad; Monperrus, Mathilde; Kadlecova, Milada; Daye, Mirna; Amouroux, David
Abstract : The methylation–demethylation processes in sediments of the Deûle River were determined using well-established isotope experiments. Abstract : The methylation–demethylation processes in sediments of the Deûle River were determined using well-established isotope experiments. For this purpose, species-specific isotopically enriched tracers in the form of inorganic mercury IHg ( 199 Hg) and methylmercury MeHg (Me 201 Hg) were used to determine Hg dynamics in the Deûle River. Sediment cores were collected at two sampling locations chosen in the most polluted zone of the Deûle River (Northern France) in proximity of a Zn, Pb, Cu, and Ni smelter called "Metaleurop" that had closed in 2003. Site I was chosen in the vicinity of the historic smelter site and site II upstream of the Deûle River. The incubation was realized directly in the sediment cores during the 24 hour experiment under environmental conditions close to the real natural systems (the same temperature, pH, humidity, light/dark conditions, oxygen levels…). The enriched isotopes were injected by needle into different sections of the core. After incubation, the core was sliced and the concentration of Hg species was determined in each section. The highest methylation potentials were found at sediment depths away from the sediment–water-interface. At site I, the methylation potential varied between 0.02–0.9% and at site II between 0.001–0.2%. The demethylation potentials fluctuated between 0.001–60% at site I and between 4–53% at site II. In both sites, negative net methylation potentials were obtained in several sediment depths, representing a net sink for MeHg. The average net methylation potential in site I demonstrated a negative value of 1919 ng g −1 day −1 . It seems that in site I the demethylation process predominates methylation. Whereas, in site II, the average net methylation potential was a positive value of 138 ng g −1 day −1, demonstrating the dominance of methylation over demethylation.